Thinking Mathematically (6th Edition)

Published by Pearson
ISBN 10: 0321867327
ISBN 13: 978-0-32186-732-2

Chapter 6 - Algebra: Equations and Inequalities - 6.1 Algebraic Expressions and Formulas - Exercise Set 6.1: 32

Answer

-22

Work Step by Step

Given -$x^{2}$ -3xy +4$y^{3}$, x=-3, y=-1 Step 1: Put the value of x=-3 and y=-1 for each x and y in the expression =-$(-3)^{2}$ -3(-3)(-1) +4$(-1)^{3}$ Step 2: Evaluate the exponential expression$(-3)^{2}$ = (-3)(-3) = 9 $(-1)^{3}$ = (-1)(-1)(-1) = -1 =-9-3(-3)(-1)+4(-1) Step 3: Multiply 3(-3)(-1) = 9, 4(-1) = -4 = -9-9-4 Step 4: Add and Subtract from left to right first add -9-9 -18-4 = -22
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.